The Communicative Approach in Teaching Arabic Grammar for Activation and Evaluation: Department of Arabic Language and Islamic Studies at the College of Education - Tripoli as a model (The International Journal of Educational Sciences and Arts, 2025)
Codifying the language and preserving it by formulating precise and solid grammar rules is a great work undertaken in the past by a number of scholars who spent their effort, money and time for this, but the contemporary Arab person has become reluctant to this science, weak in comprehending it, neglecting to specialize in it, and He suffers from obvious difficulties in using language free of grammatical and syntactic errors, This is certainly due to the reasons that intensified and led to this impasse. Therefore, everything related to the study and teaching of grammar must be changed and developed, including the way it is presented. Therefore, this research dealt with a modern strategy, which is the communicative approach, and clarified its characteristics, objectives, and characteristics of its use in order to teach grammar in the theoretical aspect of it. To test the extent of what is practiced in classrooms and during the assessment of learners in the procedural part, taking the descriptive analytical approach and statistical analysis as a way.
Keywords: Arabic Language; Grammar; Approach; Communicative